Changes in the business model for Spanish fresh tomato trade - De Pablo-Valenciano, Jaime; Giacinti-Battistuzzi, Miguel A.; Tassile, Valentín; García-Azcárate, Tomás (Spanish Journal of Agricultural Research, 2017)
The business model applied to the fresh tomato trade from Almería is well known in Spain and abroad. The changes in demand are forcing export companies to change their trade strategies to become or remain competitive. The purpose of this paper is to know the business structure and its export dynamics in addition to the changes in trade strategies made by companies in Almería during the 2009-2013 period. The methodology is based on the Herfindahl-Hirshman index and the foreign trade competitiveness index, whereas the congruence analysis is based on Pearson’s correlation coefficients and the RV coefficient. We have also applied the dual multiple factor analysis to verify changes made to the trade policy in leading businesses between two periods or scenarios. The research shows that export-driven companies behave as a moderately concentrated structure and there is an increase in the number of exporters. The competitiveness map for Almería reveals the sector’s trend with regard to the most important markets. We have verified the changes made to their trade strategy to adjust to changes in foreign trade between the 2008/09 and 2012/13 campaigns. Finally, it can be pointed out that, in the analyzed period, changes in the business model for fresh tomato trade of Almería have not been significant, being its structure of moderate concentration. In addition, the great majority of variations in strategies of companies to adapt to the competitive environment have been made by leading companies.